STUDI KELAYAKAN PENGGUNAAN MESIN DIESEL DENGAN METODE BREAK EVEN POINT (BEP) DAN ANALISIS SENSITIVITAS PADA PLTD (Studi Kasus : PT PLN Persero Sektor Pembangkitan Lombok PLTD Ampenan) - Made Wijana; A.A. Alit Triadi; Lalu Syahrul Anwar (Dinamika Teknik Mesin, 2016)
This study intended to analyze the feasibility of the use of the Power Plant (PLTD) of Ampenan using the break even point (BEP) and sensitivity analysis. That there are several alternatives that can be taken are: first, if the use of the selling price to the public's ability to     Rp. 800 per kWh and a subsidy of Rp. 29.758.612.278 per month, then power plant will have a turnover in the  month to 12 to earn a revenue of Rp. 159.148.857.478. Secondly, if the use of the selling price to Rp. 900 per kWh and a subsidy of Rp. 28.100.809.978 per month, then power plant  will have a turnover in the month to 12  to earn a revenue of Rp. 179.042.464.663. Thirdly, if the use of the selling price to Rp. 1000 per kWh and a subsidy of Rp. 26.443.007.678 per month, then power plant will have a turnover in the month to 12 to earn a revenue of        Rp. 199.936.071.847. Then the results of research using sensitivity analysis to changes in the initial investment is known that the increase in initial investment 600,83% below power plant  is still feasible to operate.. But the power plant  would not be feasible to operate when the increase 600,83% above the initial investment.Furthermore the sensitivity analysis to changes in income are known to decrease in revenue of less than 85,73% of power plant is still worth operating.  But if the decline in revenue was down more than 85,73% power plant operation is not feasible.